Correlates of Psychological Distress Among Pakistani Adults During the COVID-19 Outbreak: Parallel and Serial Mediation Analyses - Ashraf, Farzana; Zareen, Gull; Nusrat, Aasia; Arif, Amna; Griffiths, Mark D. (Frontiers in Psychology, 2021)
ABSTRACT Objective: The global outbreak of COVID-19 has greatly affected individual's lives around the world and resulted in various negative psychological consequences. During the pandemic, reflection and attention to COVID-19 may help in dealing with its symptomology but frequent and persistent thoughts about the situation can be unhealthy. The present study examined the direct and indirect associations between obsession concerning COVID-19, psychological distress, life satisfaction, and meaning in life. Design: The present study presents a primary analysis of normative data collected after the initial outbreak of COVID-19 in Pakistan. Parametric bootstrapping was used to test the mediation models of subjective well-being, the extent of the effect, and meaning in life as parallel and serial mediators concerning the associations between COVID-19 obsession and psychological distress measures. Setting: A sample of 1002 adults (45% men and 55% women) were recruited utilizing an online survey between April to May 2020. They were aged between 19 to 45 years (M=24.30, SD=7.29) and normalized on population characteristics. Results: Two out of three mediators fully mediated the relationship between obsession and psychological distress (total effect=.436, SE=. 053, p<.0001) illustrating that high-level obsessions were associated with low levels of satisfaction with life and meaning in life. Psychological distress is likely to decrease in the presence of a high level of satisfaction with life and meaning. Moreover, satisfaction with life and meaning in life significantly mediated the association between COVID-19 obsession (z=-3.471, p<.0001 and z=-2.788, p<.001 respectively). Conclusion: The present study showed that life satisfaction and meaning in life may play a significant role in decreasing psychological distress during the COVID-19 pandemic.